PEMULIAAN BIBIT TANAMAN KANTONG SEMAR (Nepenthes mirabilis) DALAM UPAYA KONSERVASI DENGAN PENAMBAHAN HORMON MELALUI TEKNOLOGI MODERN KULTUR JARINGAN - Nurokhman, Amin; Aryani, Fina; Bintang Saputri, Tegar; Qonita Zhafira, Faizah (STIGMA: Jurnal Matematika dan Ilmu Pengetahuan Alam Unipa, 2026)
Nepenthes mirabilis is an endemic plant of Sumatra that has been classified as endangered since 2014. This plant needs to be conserved to prevent its extinction. One of the methods that can be applied to overcome the threat of extinction is plant propagation through modern tissue culture technology. Using this method, plant breeding can be carried out in a relatively short time, in large quantities, and without depending on seasonal conditions. The aim of this research is to conserve this rare species through experimental approaches using a completely randomized design. The data were analyzed both descriptively and quantitatively. In this study, variations of kinetin hormone concentrations were applied (0 ppm, 0.25 ppm, 0.50 ppm, 0.75 ppm, 1.0 ppm, 1.25 ppm, 1.50 ppm, 1.55 ppm, and 2.00 ppm). The best results were obtained at a concentration of 1.50 ppm, with the highest average number of leaves (8.00 ± 0.000) and the longest leaf length (8.083 ± 0.022 cm). These findings indicate that the application of kinetin at certain concentrations can accelerate the propagation of Nepenthes mirabilis seedlings in vitro, producing more plantlets in a shorter period of time, and without seasonal limitations. Therefore, tissue culture techniques with the addition of kinetin hormone can serve as an effective solution to support the conservation and sustainable propagation of Nepenthes mirabilis.   Keywords: conservation, Hormone, pitcher plant, propagation, tissue culture